Strength And Durability Properties Of Lightweight Foamed Concrete For Housing Construction - Zulkarnain, Fahrizal (2011)
Foamed concrete is either cement paste classified as lightweight concrete, where air-voids are entrapped in mortar by a suitable foaming agent. It possesses high-flow ability, low self-weight, minimal consumption of aggregate, controlled low strength, and excellent thermal insulation properties. A wide range of densities of the foam concrete between (1600-400 kg/m3), with proper control in the dosage of the foam, can be obtained for the structural, partition, insulation application and the filling grades. In this research, foam concrete uses fine aggregate passing a 5 mm or 3/16 inch sieve, and 10% of Norizal Hardener Powder Code: 4 (NHP4) based on the weight of cement, for increasing the strength and durability of lightweight foamed concrete.